Benchmarking of fluorescence cameras through the use of a composite phantom - Gorpas, Dimitris; Koch, Maximilian; Anastasopoulou, Maria; Klemm, Uwe; Ntziachristos, Vasilis (Journal of Biomedical Optics, 2017)
Fluorescence molecular imaging (FMI) has shown potential to detect and delineate cancer during surgery or diagnostic endoscopy. Recent progress on imaging systems has allowed sensitive detection of fluorescent agents even in video rate mode. However, lack of standardization in fluorescence imaging challenges the clinical application of FMI, since the use of different systems may lead to different results from a given study, even when using the same fluorescent agent. In this work, we investigate the use of a composite fluorescence phantom, employed as an FMI standard, to offer a comprehensive method for validation and standardization of the performance of different imaging systems. To exclude user interaction, all phantom features are automatically extracted from the acquired epi-illumination color and fluorescence images, using appropriately constructed templates. These features are then employed to characterize the performance and compare different cameras to each other. The proposed method could serve as a framework toward the calibration and benchmarking of FMI systems, to facilitate their clinical translation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: benchmarking; fluorescence imaging; rigid phantom; standardization